A Cross-sectional study on the transmission dynamics of Bovine Herpesvirus-1 infection in the farms located in the Thrace Region of Turkey - Ünver Alçay, Ayla; Yilmaz, Huseyin (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, detection of BHV-1 infections in cattle by using polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) and investigation of the risk factors associated with the spread of the virus within the herd were aimed. Three dairy farms were selected in the Thrace district, Marmara region, Turkey, and two visits to these farms. A questionnaire was prepared for the farmers. On the first visit, 4 (14.81%) of 27 animals on Farm 1, 6 (28.57%) of 21 animals in farm 2, and 3 (7.31%) of 41 animals in Farm 3 were found to be seropositive for BHV-1. On the second visit, 6 (25%) of 24 animals in Farm 1, 6 (35.29%) of 17 animals in Farm 2, and 6 (20%) of 30 animals in Farm 3 were found to be seropositive for BHV-1. Thirteen (14.6%) of 89 blood samples were seropositive at the first sampling and 18 (25.35%) of 71 blood samples in the second sampling. Two calves belonging to 7 cows that were found to be seropositive at the first visit, and the calves of four of 10 mothers found to be seropositive at the second visit were also found seropositive. BHV-1 DNA was detected in only 3 of the 43 milk samples taken during the first and second visits (2 on the first visit, one on the second visit), and 13 of 160 nasal swabs (8 on the first visit, five on the second visit). All the cows with three milk samples whose BHV-1 DNA was detected by PCR were determined as seropositive. Three of the eight cattle with BHV-1 DNA detected in nasal swabs on the first visit, and 4 of the five cattle with BHV-1 DNA detected in nasal swabs on the second visit were detected seropositive by ELISA. The statistical analysis has shown that the association between age, sex, and BHV-1 seropositivity was statistically significant. The BHV-1 seroprevalence was increased in animals on the second visit in all farms. The preventive measurements need to be applied in Turkey to control BHV-1 infections in cattle.